Four new species of the leafhopper genus Riseveinus Li (Hemiptera: Cicadellidae: Evacanthinae) from China and Thailand - Wang, Yang; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2018)
The Oriental leafhopper genus Riseveinus Li is recorded from Thailand for the first time. Four new species, R. cervcornutus sp. nov., R. hamatus sp. nov., R. spinatus sp. nov. and R. tenuispinus sp. nov., are described and illustrated. Their diagnostic characteristics are compared with close relatives. A key to all known species of Riseveinus is provided.